Potential of Mesenchymal Stem Cells in Anti-Cancer Therapies - Kostadinova, Milena; Mourdjeva, Milena (Current Stem Cell Research & Therapy, 2020)
Mesenchymal stem/stromal cells (MSCs) are localized throughout the adult body as a small population in the stroma of the tissue concerned. In injury, tissue damage, or tumor formation, they are activated and leave their niche to migrate to the site of injury, where they release a plethora of growth factors, cytokines, and other bioactive molecules. With the accumulation of data about the interaction between MSCs and tumor cells, the dualistic role of MSCs remains unclear. However, a large number of studies have demonstrated the natural anti-tumor properties inherent in MSCs, so this is the basis for intensive research for new methods using MSCs as a tool to suppress cancer cell development. This review focuses specifically on advanced approaches in modifying MSCs to become a powerful, precision- targeted tool for killing cancer cells, but not normal healthy cells. Suppression of tumor growth by MSCs can be accomplished by inducing apoptosis or cell cycle arrest, suppressing tumor angiogenesis, or blocking mechanisms mediating metastasis. In addition, the chemosensitivity of cancer cells may be increased so that the dose of the chemotherapeutic agent used could be significantly reduced.
Keywords: cell cycle arrest